Pengelolaan Sanitasi Pada Pemerintah Lokal: Studi Kasus Peningkatan Kelembagaan Prasarana Instalasi Pengolahan Lumpur Tinja Kabupaten Ponorogo - Yuanita, Mike; Syahbiba, Ismy Nur; Haryono, Nanang (Journal of Governance and Administrative Reform, 2021)
AbstractSanitation management is an important part of sustainability in line with the Sustainable Development Goals (SDGs). For this reason, the Directorate General of Human Settlements (IPLT) has built an infrastructure for sewage treatment plants (IPLT) in an effort to increase public access to sanitation services. For optimal and sustainable IPLT, it is necessary to separate the functions of regulator and operator managing the sanitation sector through institutional development of the technical implementing unit (UPTD). The focus of the discussion of this article is on the analysis of the institutional development of the UPTD for the management of IPLT Infrastructure in Ponorogo Regency in 2021. The results of the research are that institutional development is running according to the SE Ministry of Home Affairs No 061/4338/OTDA concerning Consultation Guidelines for the Establishment of Branch Offices and UPTDs, however, in the consultation process for KA UPTD PALD Ponorogo Regency at the Bureau of Organization of East Java Province was delayed because of the "Acceleration Process for Equalization of Positions in the Regional Government Environment" agenda by the Ministry of Home Affairs as stated in a Circular from the Ministry of Home Affairs Number 800/6078/OTDA. This process requires coordinationKeywords: sanitation, local government, institutionsAbstrakPengelolaan sanitasi menjadi bagian penting untuk keberlanjutan sejalan dengan Sustainable Development Goals (SDGs). Untuk hal tersebut infrastruktur instalasi pengolahan lumpur tinja (IPLT) telah dibangun oleh Direktorat Jenderal Cipta Karya upaya meningkatkan akses masyarakat terhadap layanan sanitasi. Untuk optimal dan berkelanjutan IPLT maka perlu pemisahan fungsi regulator dan operator pengelola bidang sanitasi melalui pengembangan kelembagaan unit pelaksana teknis dinas (UPTD). Fokus pembahasan artikel ini pada analisis pengembangan kelembagaan UPTD untuk pengelolaan Prasarana IPLT Kabupaten Ponorogo tahun 2021. Hasil penelitian adalah pengembangan kelembagaan berjalan sesuai SE Kemendagri No 061/4338/OTDA tentang Pedoman Konsultasi Pembentukan Cabang Dinas dan UPTD namun demikian, pada proses konsultasi KA UPTD PALD Kabupaten Ponorogo pada Biro Organisiasi Provinsi Jawa Timur tertunda karena adanya agenda "Akselerasi Proses Penyetaraan Jabatan di Lingkungan Pemertintah Daerah” oleh Kemendagri sebagaimana tertuang dalam Surat Edaran dari Kementerian Dalam Negeri Nomor 800/6078/OTDA. Pada proses ini perlu koordinasi.Kata kunci: sanitasi, pemerintah lokal, kelembagaan